Peran Dinas Sosial Dalam Pemberdayaan Kampung Pengemis Kota Sukabumi - Munandi Saleh; Robi Ananda Prayoga (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2025)
The Sukabumi City Social Service has a strategic role in empowering beggars through various rehabilitation and social assistance programs. However, the effectiveness of these programs is still questionable, given the still significant number of beggars and the low level of their participation in empowerment programs. Therefore, this study aims to analyze the role of the Social Service in empowering beggar villages in Sukabumi City, identify the types of programs that have been implemented, and evaluate their effectiveness and the obstacles faced. This study uses a descriptive qualitative method with data collection techniques in the form of in-depth interviews, field observations, and documentation. The informants in this study consisted of employees of the Sukabumi City Social Service who were involved in the empowerment program as well as representatives of the begging village community. The data was analyzed using interactive qualitative analysis methods that included data reduction, data presentation, and conclusion drawn. The results of the study show that the Social Service has carried out various empowerment efforts through preventive, rehabilitative, and social assistance approaches. Preventive efforts are carried out through socialization and education to the community, while rehabilitation is carried out by providing skills training, mental and legal guidance, as well as social rehabilitation services. In addition, social assistance such as the Family Hope Program (PKH) and Non-Cash Food Assistance (BPNT) are also given to the poor.